2020
DOI: 10.1002/aelm.202000306
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin, Stretchable, and Breathable Epidermal Electronics Based on a Facile Bubble Blowing Method

Abstract: Developing epidermal electronics for physiological signal monitoring, including human biopotential (electroencephalogram [EEG], [1,2] electrocardiogram [ECG], [3-6] and electromyogram [EMG] [7-9]) and vibration (pulsation [10,11] and voice [12,13]) signals, is of great importance for next-generation wearable medicine, human-computer interaction, and smart robot applications. In general, most reported flexible electronics exploit plastic or elastic matrices (PET, PI, PDMS, Ecoflex, parylene, etc.) with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 56 publications
0
62
0
Order By: Relevance
“…Kim et al [26] developed a stretchable, ultrathin, transparent electronic skin. And the function was tested with ECG sensing and strain sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [26] developed a stretchable, ultrathin, transparent electronic skin. And the function was tested with ECG sensing and strain sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(ethylene terephthalate) and poly(ethylene naphthalate) foils process as lightweight as 3 gm ‐2 with the thickness of 1.4 μm, enabling to stand on soap bubbles 47,48 . Due to the gas permeability limitation of the planar substrate, nano network structures by electrospinning gained popularly 24 . The typical gold nanomesh conductor as thin as 70 nm developed by Miyamoto et al 26 showed considerable gas permeability compared with the unencapsulated bottle and weak anaphylaxis on the skin of forearm (Figure 2E).…”
Section: Requirements and Designs For Conformal On‐skin Electrodesmentioning
confidence: 99%
“…Generally, there are two strategies to fabricate epidermal electronics. The first method is to fill polymer composites with conductive materials, such as carbon nanotubes, graphene, and metal nanowires [10][11][12][13][14][15][16] , while the other method uses metals with designed structures, including serpentine and accordion bellow shapes [17][18][19] . Metal-based devices take advantage of their electrical conductivity compared with their polymer-based counterparts.…”
Section: Introductionmentioning
confidence: 99%